Development of an English Learning Model Based on Multimedia at MTS Darul Falah Ternate - Supriyadi, Agus; Anwar, Indry Widyasti; Octasary, Magvirah; Wahjuningsih, Eka; Tapain, Sitinur Ajijah; Tauda, Sulasti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the pedagogical model developed in relation to the mission of the MT language group. Overall, the research was carried out using the R & D method through 4-D steps: define, design, develop, expand, and disseminate (Thiagarajan, 1974). From these 4-D steps, the first three steps in developing learning models were carried out in the first year after experiments were carried out in previous research in 2023. Furthermore, the teaching development guide manuscript was still carried out in the second year. In the second year, the teaching models that have been tested still undergo a further development stage to perfect them, and then they are tested again on a larger scale. The results in the third year will undergo the dissemination stage. The manuscript for the Guide to Developing a Multimedia-Based Teaching Model will be subjected to a limited trial to obtain input as material for improvement. So, this manuscript is still in the development stage, which will be followed by the dissemination stage in the third year